The Direct Oblique Method: A New Gold Standard for Bronchoscopic Navigation That is Superior to Automatic Methods. Issue 4 (October 2018) - Miyake, Kotaro; Morimura, Osamu; Inoue, Takako; Yoshida, Kenya; Nagatomo, Izumi; Kijima, Takashi; Kumanogoh, Atsushi
Abstract : Background: The purpose of this study was to identify bronchi on computed tomographic (CT) images, manual analysis is more accurate than automatic methods. Nonetheless, manual bronchoscopic navigation is not preferred as it involves mentally reconstructing a route to a bronchial target by interpreting 2-dimensional CT images. Here, we established the direct oblique method (DOM), a form of manual bronchoscopic navigation that does not necessitate mental reconstruction, and compared it with automatic virtual bronchoscopic navigation (VBN). Methods: Routes were calculated to 47 identical targets using 2 automatic VBNs (LungPoint and VINCENT-BFsim) and the DOM, using 3 general application CT viewers (Aquarius, Synapse Vincent, and OsiriX). Results of all analyses were compared. Results: The DOM drew routes to more targets than the VBNs [94% (the DOM on any viewer) vs. 49% (LungPoint) vs. 62% (VINCENT-BFsim), P <0.0001]. For the 44 targets with the CT-bronchus or CT-artery signs, 100% of the DOM routes led to targets. In the bronchoscopic simulation phase, the DOM covered 100% of the bifurcations identified on CT, whereas some bifurcations were skipped and some bronchial walls appeared partially transparent in the VBNs. Manual analysis identified more bronchi near the targets than the VBNs [32.1±3.4 (manual analysis) vs.18.9±2.1 (LungPoint) vs. 22.9±2.7 (VINCENT-BFsim), mean±SEM, P <0.0001]. The DOM took around 5 minutes on average. Conclusion: On the basis of precise manual CT analysis using general application CT viewers, the DOM drew routes leading to more targets and provided better bronchoscopic simulation than the automatic route calculation of the VBNs. Abstract : Supplemental Digital Content is available in the text.